Penguatan Literasi Sastra Religi Melalui Pendidikan Hadrah: Kreativitas Pemuda Desa Karangrejo Kecamatan Gumuk Mas, Jember dalam Menciptakan Syair Islami” - Furoidatul Husniah; Akhmad Taufiq; Sukatman Sukatman; Fitri Nura Murti; Inno Cahyaning Tyas; Siwi Tri Purnami; Adenarsy Avereus Rahman (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The community service program in Karangrejo Village, Gumukmas District, Jember, focuses on strengthening religious literary literacy through hadrah education and Islamic syiiran. This initiative was driven by the limited creativity of local youth in composing new religious lyrics and the absence of systematic strategies for digitalization and promotion of Islamic arts. The program was carried out through observation, problem mapping, Focus Group Discussions (FGD), training, and intensive mentoring for four months. The results show that the Majelis Sholawat Mansub Ratibul Haddad community has successfully developed independence in creating new religious lyrics inspired by stories of Uwais Al-Qarni, Sunan Kalijaga, Qorun, and KH. Ahmad Shiddiq. This creative process demonstrates the transformation of religious narratives into oral literary works with educational, spiritual, and aesthetic functions. The outcomes confirm that participatory facilitation empowers village youth to become producers of new works rather than mere consumers of tradition. These findings highlight the importance of religious literary literacy as a medium to strengthen cultural identity, revitalize moral values, and promote community-based religious edutourism.